Factors associated with Ascaris Lumbricoides and Trichuris Trichiura infection among 5-9 years old children in selected urban poor areas of the Philippines - Pham Ngan Giang
The cross-sectional study utilized the data from the Urban Health Nutrition Project survey which was conducted from July to September of 1995. Four hundred and ninety two children from 5-9 years old were recuited into the study. The objective of the study was to determine the relationship between selected environment factors and Ascaris Lumbricoids and Trichuris Trichiuria infection.There was not enough evidence for the relationships between the following variables and helminthic infection: garbage disposal (OR=0.52 and 95CI=0.24 - 1.13; OR=1.69 and 95CI=0.81 - 3.51), type of florr (OR=1.48 and 95CI=0.55-4.03; OR=0.32 and 95CI=0.09-1.12), source of water (OR=0.90 and 95CI=0.56-1.43).The presence of toilet in the households was found to have a significant effect with helminthic infection status. Children who lived in the households without toilet had a higher chance to getting helminthic infection as compared with those who lived in the households with toilet (OR=2.56 and 95CI=1.46-4.48).For extraneous variables, family income was found to have a significant association with helminthic infection. There was not enough evidence to support the association between family crowding index, age and sex of children and helminthic infection.Integration between mass treatment and environmental improvement is recommended for a parasite control program. Further studies should be implemented in order to make clear the relationship between environmental factors and helminthiases in different areas.
Thesis (Master of Science in Epidemiology)--University of the Philippines Manila.
Keywords: Ascaris; Trichuriasis; Helminthiasis; Ascaris lumbricoids